PENGABULAN PERMOHONAN IZIN POLIGAMI DITINJAU DARI PRESPEKTIF HUKUM ISLAM (STUDI KASUS NOMOR PERKARA 466/Pdt.G/2020 DI PENGADILAN AGAMA KABUPATEN MALANG) - Fatimatus Zahroh; Ahmad Subekti; Abdul Wafi (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2022)
Polygamy is a marriage system in which one party has or marries several members of the opposite sex at the same time. Termologically, polygamy can be understood as a condition where a husband has more than one wife. A polygamous husband can have two, three, four wives at the same time. Basically the permissibility of polygamy is absolute and fair, it is an obligation for husbands to their wives and children because of religious demands. Second, the approval of the wife is the most important thing in the case of a polygamy application which will later be considered by the judge in granting or refusing a polygamous permit for a polygamist. Third, the most important requirement in considering polygamy is financial ability. When a husband decides to remarry, the first thing that should come to his mind is the issue of the responsibility for living and living for two families at once. Livelihood, of course, does not stop just being able to feed and drink for his wife and children, but more than that how he planned the living expenses budget down to the issue of proper education, housing and all other necessities. Making the decision of the Malang Regency Religious Court Number 466/Pdt.G/2020/PA.Kab.Mlg as the main analysis material. Kata kunci:Acceptance, Polygamy, Islamic Law.